Pharmacokinetics, pharmacodynamics and safety of the inverse retinoic acid‐related orphan receptor γ agonist AZD0284. Issue 7 (3rd March 2020) - Asimus, Sara; Palmér, Robert; Albayaty, Muna; Forsman, Henrik; Lundin, Christina; Olsson, Marita; Pehrson, Rikard; Mo, John; Russell, Muir; Carlert, Sara; Close, David; Keeling, David
Abstract : Aims: Retinoic acid‐related orphan receptor γ (RORγ), a master regulator of T‐helper 17 (Th17) cell function and differentiation, is an attractive target for treatment of Th17‐driven diseases. This first‐in‐human study aimed to investigate the pharmacokinetics, pharmacodynamics, safety and tolerability of the inverse RORγ agonist AZD0284. Methods: We conducted a phase I, randomized, single‐blind, placebo‐controlled, two‐part, first‐in‐human study with healthy subjects receiving single (4–238 mg) or multiple (12–100 mg) oral doses of AZD0284 or placebo after overnight fasting. Subjects in the one single dose cohort additionally received a single dose of AZD0284 after a high‐calorie meal. AZD0284 plasma concentrations, as well as inhibition of ex vivo‐stimulated interleukin (IL)‐17A release in whole blood, were frequently measured after both single and multiple dosing. Results: Eighty‐three men participated in the study. AZD0284 was absorbed rapidly into plasma after oral dosing and exhibited a terminal half‐life of 13–16 hours. Both the area under the concentration‐time curve (AUC) and maximum concentration ( C max ) increased subproportionally with increasing dose (95% confidence intervals of slope parameter were 0.71–0.84 and 0.72–0.88 for AUC and C max, respectively). Food intake delayed the absorption of AZD0284 but did not affect the overall exposure or half‐life. AZD0284 showed dose‐dependent reduction of ex vivo‐stimulated IL‐17A release after both single and multiple doses. No significant safety concerns were identified in the study. Conclusions: AZD0284 was well tolerated, rapidly and dose‐dependently absorbed, and reduced stimulated IL‐17A release after single and multiple dosing. The results of this study support further clinical development of AZD0284.